State of solid waste disposal and suggested fixes for Iwo and Ibadan Metropolis, Nigeria - Jazat, J. P.; Akande, J. A.; Ogunbode, T. O. (Frontiers in Sustainability, 2023)
Factors governing stakeholders choice of gathering and disposing solid wastes in some south-western states of Nigeria were appraised using Iwo and Ibadan as case studies. The objectives were to determine associated challenges and recommend possible improvements. The study administered 1,400 structured questionnaire out of which were 873 (62.3%) respondents. Data obtained were analyzed using descriptive and inferential statistics and the result showed upward trend in solid waste disposal in the two communities with stakeholders’ income and household size. Solid wastes generally encountered in the study areas include foods, leaves, papers, clothing, leather, hair attachments, nylons, plastics, metals and cans which often litter the dump environment. Economic cost of a sack-load of waste was *N200 in Iwo and N495 in Ibadan and the frequency of waste removal is 150% higher in Iwo than in Ibadan. Average distance to the dumpsite is 2km and is a disincentive to low-income earners that are majorly pedestrian. Ibadan residents are culturally disposed to dirty streets and drainage/gutters with solid wastes; unfortunately, the situation in Iwo is not different. Stakeholder perception of factors impacting waste disposal in Iwo, gave greater weight to: (1). Income and spending power (2). Culture (3). Religion (4) Governmental intervention (5). Health factors in that order. In Ibadan, (1). Income and spending power (2). Health factors (3). Occupational hazards and (4). Religion was rated in that sequence. It is conjectured that these issues demand strong attention in efforts to build functional capacities for solid waste disposal.